The Position of Article 23 of the Corruption Criminal Act After the Enactment of the National Criminal Code - Sirjon, Lade; Yan Fathahillah Purnama; La Ode Muhamad Sulihin; La Ode Muhammad Taufiq Afoeli; Risma Yulestari (As-Siyasi: Journal of Constitutional Law, 2025)
Enforcing criminal law against corruption in Indonesia faces significant challenges due to the dynamics of legal change, particularly following the enactment of Law No. 1 of 2023 on the National Criminal Code. This study aims to analyze how the principles of legality and lex favor reo, as applied to the interpretation of criminal provisions, affect the consistency of law enforcement, particularly in the context of Article 23 of the Law on the Eradication of Corruption, which refers to several provisions of the old Criminal Code. Using a normative legal research method with a conceptual approach and a comparative analysis of court decisions, data are collected through literature reviews and regulatory analysis. The research findings indicate that changes in the normative reference of primary norms in the National Criminal Code have led to significant differences in the criminal threats and criminal provisions referenced in Article 23 of the Law on the Eradication of Corruption. The application of the lex favor reo principle becomes crucial, as the most lenient provisions are applied not only to the defendant but also in the context of the National Criminal Code, where the terminology is expanded to include the concepts of the perpetrator, accomplice, suspect, defendant, and convict. The consistency of the Supreme Court in adhering to a material theory limited to the interpretation of "changes in legislation" underscores the protection of individual rights. A comprehensive harmonization and synchronization between the National Criminal Code and the Law on the Eradication of Corruption is essential to prevent normative conflicts and to ensure legal certainty in the implementation of Article 23 of the Law on the Eradication of Corruption.